New polarimetric study of the galactic X-ray burster GX 13+1 - Bobrikova, Anna; Di Marco, Alessandro; La Monaca, Fabio; Poutanen, Juri; Forsblom, Sofia V.; Loktev, Vladislav (EDP Sciences, 2025)
Weakly magnetized neutron stars (WMNSs) are complex astrophysical objects with challenging phenomenology. For decades, they have been studied via spectrometry and timing analyses. It is well established that the spectrum of WMNSs consists of several components traditionally associated with the accretion disk, the boundary or spreading layer, and the wind, along with their interactions. Since 2022, WMNSs have been actively observed using the Imaging X-ray Polarimetry Explorer (IXPE). Polarimetric studies have provided new information about the behavior and geometry of these sources. One of the most enigmatic sources in this category, the galactic X-ray burster GX 13+1, was first observed with IXPE in October 2023. A highly variable polarization at levels of 2–5% was detected, with the source showing a rotation of the polarization angle (PA), suggestive of misalignment within the system. A second observation was performed in February 2024, complemented by observations from Swift/XRT. IXPE measured an overall polarization degree (PD) of 2.5% and a PA of 24°, while Swift/XRT data helped us evaluate the galactic absorption and fit the continuum. Here, we study the similarities and differences in the polarimetric properties of the source during the two observations. Our findings confirm the expected misalignment in the system and the assignment of the harder component to the boundary layer. We also emphasize the significance of the wind in the system. Additionally, we observe notable differences in the variation of polarimetric properties with energy and over time.